Review of the Second Five Year Plan - Planning Commission (Planning Commission)
This document gives a survey of the achievements of our State in respect of the Second Five-Year Plan. Details of various schemes have been given under each head of Development. A narrative note is given in Part I of this publication. The achievements as well as details of expenditure for the five years of the Plan period, are summarized in a tabular form in Part II. During the Second Plan, the State has laid emphasis on food production and expansion of industrial opportunities through Power Development. At the commencement of the Second Plan, the food production of the re-organized Madras State stood at roughly 44 lakhs tons.
Madras State